Bio inspired microfluidic-based analysis of Klebsiella pneumoniae virulence factors and antimicrobial resistance - Xiaoping Song; Jun zhang; Weihong Hua; Yan Zheng; Xiaolin Liu; Yuanqi Zhu; Sun Bin; Jian Ding; Suling Sun (SLAS Technology)
The objective of this research was to examine the antibiotic resistance and microbiological traits of Klebsiella pneumoniae isolates that were responsible for liver abscesses in Qingdao, China. Between April and September 2022, isolates were taken from 120 patients at three tertiary hospitals. Rapid detection of capsule serotypes (K1, K2) and virulence genes (rmpA, aerobactin) was achieved by using microfluidic-based techniques. Testing for antimicrobial susceptibility was done with the VITEK 2 Compact system. The findings showed that there was a high frequency of extremely virulent K. pneumoniae strains, which are often linked to bacteremia and higher death rates. These strains belonged to the K1 and K2 serotypes and were primarily carrying the aerobactin and rmpA genes. The majority of isolates were antibiotic-sensitive, but the emergence of resistant strains emphasizes the necessity of continuing surveillance. The efficiency of microfluidic platforms for the quick and precise characterization of K. pneumoniae is demonstrated in this work, enabling prompt clinical interventions.